Nonextraction Treatment of Severe Crowding with the Aid of Corticotomy-Assisted Orthodontics - Ali S. Aljhani; Khalid H. Zawawi (Hindawi Limited, 2012)
This paper illustrates the combined nonextraction orthodontic treatment with the corticotomy technique in an adult patient (age: 25 years and 3 months) with severely crowded arches to accelerate tooth movement and shorten the treatment time. Both her upper lateral incisors were congenitally absent and both upper central incisors' roots were short. Initial fixed orthodontic appliances (bidimensional) were bonded and one week later buccal and lingual corticotomy with alveolar augmentation procedure in the maxilla and mandible was performed. Orthodontic activation to level and align and unravel the crowding was performed every two weeks. The total treatment time was 8 months with no adverse effects observed at the end of active treatment. The addition of the decortication procedure to the conventional orthodontic therapy decreased the duration of treatment significantly. Successful alignment of both arches with ideal overbite and overjet as well as adequate occlusion was achieved.